MENELISIK REVITALISASI PENDIDIKAN AGAMA ISLAM DALAM KONSEP IBNU AL QAYYIM AL-JAUZIYYAH (1292-1350 M) - Ni’mah, Zetty Azizatun (Edudeena : Journal of Islamic Religious Education, 2018)
Abstract: The concept of Islamic education perspective Ibn Qayyim very relevant once applied in Islamic education in Indonesia. Character building through PAI has been very in harmony with the concept of manhaj tarbiyah offered by Ibn Al Qayyim Al Jawziyah with educational goals that include ahdaf akhlaqiyah, ahdaf jismiyyah, ahdaf Fikriyh and ahdaf maslakiyah. Like wise with the target 9 aspects that cover all disciplines with no character or akhlakul karimah left on every students. Problems that arise in the PAI either on the conceptual problem or the application problem in which das sollen PAI as an agent of character formation but das sein failed. For that need to revitalize PAI so that initial steps as character formers can be realized. In this case the concepts offered by Ibn Al Qayyim Al Jauziyyah could be the basis for educational policy makers and Muslim educators.   Abstrak: Konsep pendidikan Islam perspektif Ibnu Qayyim masih relevan diaplikasikan dalam pendidikan Islam yang ada di Indonesia. Pembangunan karakter melalui PAI sudah sangat selaras dengan konsep manhaj tarbiyah yang ditawarkan oleh Ibnu Al Qayyim Al Jauziyah dengan sasaran 9 aspeknya yang mencakup seluruh disiplin ilmu dengan tanpa meninggalkan karakter atau akhlakul karimah pada setiap peserta didik. Problem-problem yang muncul pada PAI baik pada problem konseptual atau problem aplikasinya yang mana das sollennya PAI sebagai agen pembentukan karakter tapi das seinnya mengalami kegagalan. Untuk itu perlu adanya revitalisasi PAI agar khittah awal sebagai pembentuk karakter bisa terealisasikan. Dalam hal ini konsep-konsep yang ditawarkan Ibnu Al Qayyim Al Jauziyyah bisa dijadikan dasar bagi para pembuat kebijakan pendidikan dan para pendidik Muslim.